1996
DOI: 10.1016/s0092-8674(00)81084-3
|View full text |Cite
|
Sign up to set email alerts
|

Sec18p (NSF)-Driven Release of Sec17p (α-SNAP) Can Precede Docking and Fusion of Yeast Vacuoles

Abstract: S. cerevisiae inherits its vacuole by projecting vacuole-derived membrane vesicles and tubules into the bud, where they fuse to establish the daughter vacuole. This homotypic fusion event can be assayed in vitro. It requires Sec17p and Sec18p, the homologs of the mammalian alpha-SNAP and NSF, which cooperate in multiple steps of membrane trafficking. We now report that Sec17p, Sec18p, and ATP are only needed for an early stage of the reaction that results in Sec17p release. Sec17p and Sec18p actions precede, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
635
1
9

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(671 citation statements)
references
References 60 publications
26
635
1
9
Order By: Relevance
“…Consistent with this possibility, syntaxin 3 (but not coexpressed syntaxin 2 or 4) has been localized to zymogen granules in pancreatic acinar cells (Gaisano et al, 1996), recycling tubulovesicles in gastric parietal cells (Bennett, manuscript in preparation) and secretory granules in eosinophils (Bennett, unpublished data). Recent data indicate that under certain circumstances, NSF acts solely on transport vesicles, prior to docking or fusion of these vesicles with their target (Mayer et al, 1996;Steel et al, 1996). This raises the possibility that v-SNAREs and t-SNAREs may interact on the same transport vesicle.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, syntaxin 3 (but not coexpressed syntaxin 2 or 4) has been localized to zymogen granules in pancreatic acinar cells (Gaisano et al, 1996), recycling tubulovesicles in gastric parietal cells (Bennett, manuscript in preparation) and secretory granules in eosinophils (Bennett, unpublished data). Recent data indicate that under certain circumstances, NSF acts solely on transport vesicles, prior to docking or fusion of these vesicles with their target (Mayer et al, 1996;Steel et al, 1996). This raises the possibility that v-SNAREs and t-SNAREs may interact on the same transport vesicle.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were resuspended in 60 l of sample buffer (62.5 mM pH 6.8,10% [vol/vol] glycerol,2% [wt/vol] SDS, 140 mM ␤-mercaptoethanol) and analyzed by SDS-PAGE and immunoblotting. Sec17p release assays were performed as previously described (Mayer et al, 1996) except that 5 g/ml recombinant Sec18p was also added. Vacuole-bound actin was examined over the course of standard fusion reactions without the addition of cytosol to limit rebinding.…”
Section: Protein Processing and Analysismentioning
confidence: 99%
“…This analysis showed that the increase in fusion is primarily due to an increase in the rate at early time points ( Figure 10A, bottom panel). To initiate membrane fusion vacuoles undergo priming, a process requiring ATP hydrolysis by Sec18p and the release of Sec17p (Mayer et al, 1996). Because the difference in fusion rates were most dramatic at early time points, we examined if priming kinetics were altered because of ERG6 induction.…”
Section: Modification Of Vacuolar Lipids Via Erg6 Inductionmentioning
confidence: 99%
“…Energy made available from the assembly of the trans-SNARE complexes is used to drive the fusion of lipid bilayers [8][9][10][11]. After membrane fusion, the adapter protein α-SNAP (soluble NSF attachment protein) and the ATPase NSF (Nethylmaleimide-sensitive factor) dissociate the cis-SNARE complexes at the expense of ATP [12,13] to free the SNAREs for the next round of membrane fusion.…”
Section: Introductionmentioning
confidence: 99%